O Guaíba, tão perto e tão longe : planejamento urbano e intervenção ambiental no aterramento da Praia de Belas (Porto Alegre, 1914-1959) - Vitagliano, Isa Mendes (2020)
Porto Alegre’s territorial position in relation to the Guaiba river attributes to this city some peculiarities, exposing advantages and disadvantages arising from this proximity. This research aims to observe how the capital of Rio Grande do Sul interacted with this natural element, present in its geographical space, during the urbanization process, until the middle of the 20th century. Based on the focus on landfill carried out on the Guaiba bank, located in the Praia de Belas region, we seek to promote an analysis of the environment’s role in face of the modernizing project that executive power has established for the city. Although the urbanization framework of Porto Alegre, under the legal form, just occured in 1959, with the institution of the first Urban Master Plan of the city, its genesis can be observed in the previous urban planning conceived in the 1910s. Attentive to the fact that, in all urban projects assigned to Porto Alegre, the landfill process in Praia de Belas shore was, from the beginning, mentioned and foreseen, despite the intentions behind each project divergent aspects. In this sense, in view of the reflections promoted by this research, it is expected that, when looking at the present moment, in which there is a commercial dispute between private institutions across the region, as well as the use of this space for the promotion of personalities in the political sphere, it is possible to have a more comprehensive understanding of this place, wich, recently, was in a situation of relative abandonment.